Manajemen Organisasi dalam Peningkatan Kinerja OSIS di MTs Ar-Rahman Nglaban Jombang - Desy Naelasari; Fitria Umi Salamah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
The purposes of this research are. To describe the performance of the OSIS at MTs Ar-Rahman Nglaban, Jombang. To describe organizational management in improving OSIS performance at MTs Ar-Rahman Nglaban Jombang. In order to know the supporting and inhibiting factors in improving OSIS performance at MTs Ar-Rahman Nglaban Jombang. This research is a qualitative field research. The method used is a qualitative method with a qualitative descriptive design with data collection techniques through observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive. The results of the study showed that: the performance of the student council at MTs Ar-Rahman Nglaban Jombang has increased compared to before seen from the enthusiastic participation of student council students in carrying out student council activities. But there are still some student council students who are lazy to participate in student council activities. Organizational management can be seen clearly from the organizational structure, where the OSIS administrators already have their respective duties and responsibilities. Through the management of this organization, they receive guidance and direction from the Head of Madrasah, Deputy Student Affairs, and OSIS Advisors. The supporting factors are teachers, parents, budget, facilities and infrastructure. While the inhibiting factors are the lack of experience in organizing, the osis administrators do not understand work and peers.